2023
DOI: 10.1113/jp284164
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of 5‐HT2 receptors suppresses motor unit firing and estimates of persistent inward currents during voluntary muscle contraction in humans

Abstract: support-information-section).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 61 publications
3
23
0
Order By: Relevance
“…Such changes could be brought about by a change in the balance of synaptic inputs driving the motoneurone pool. Consistent with this idea, 5-HT2 antagonism was found to reduce estimates of PICs during low intensity dorsiflexion contractions (Goodlich et al, 2023). This same effect may be present in the current study as 5-HT2 antagonism also reduced maximal elbow flexion torque.…”
Section: -Ht2 Antagonism Exerts Effects On Spinal Motoneurones Only W...supporting
confidence: 90%
See 1 more Smart Citation
“…Such changes could be brought about by a change in the balance of synaptic inputs driving the motoneurone pool. Consistent with this idea, 5-HT2 antagonism was found to reduce estimates of PICs during low intensity dorsiflexion contractions (Goodlich et al, 2023). This same effect may be present in the current study as 5-HT2 antagonism also reduced maximal elbow flexion torque.…”
Section: -Ht2 Antagonism Exerts Effects On Spinal Motoneurones Only W...supporting
confidence: 90%
“…Since 5-HT2 antagonism can increase measures of motor cortical inhibition (Thorstensen et al, 2021) and reduce estimates of PICs at motoneurones (D'Amico et al, 2013;Goodlich et al, 2023), we hypothesised that 5-HT2 receptor antagonism would increase intracortical inhibition, and reduce motoneurone excitability during voluntary contractions.…”
Section: Introductionmentioning
confidence: 99%
“…We observed that onset-offset hysteresis (i.e., ΔF) is greater at higher contraction levels, which suggests that the contribution of PICs to self-sustained motoneuron discharge increases as a function of contraction force. These results are consistent with prior reports in the tibialis anterior and gastrocnemius medialis muscles (Orssatto et al ., 2021; Goodlich et al ., 2023), but contrast reports of no differences in discharge rate hysteresis with increased contraction levels in tibialis anterior and soleus (Kim et al ., 2020; Afsharipour et al ., 2020). Though the reason for these conflicting findings is difficult to discern, methodological factors are plausible contributors.…”
Section: Discussionmentioning
confidence: 99%
“…However, when examined across different contraction levels, findings regarding ΔF remain inconclusive. ΔF has been shown to either increase (Orssatto et al ., 2021; Goodlich et al ., 2023) or remain constant (Kim et al ., 2020; Afsharipour et al ., 2020) with increased voluntary drive. Although monoaminergic inputs likely vary between motor pools (Hounsgaard et al ., 1988; Wilson et al ., 2015) and could conceivably explain these varied findings, inconsistencies are still reported when examining the same muscle (Kim et al ., 2020; Orssatto et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This is a big challenge because direct measures of, for example, serotonergic input onto motor neurones are properties of voltage-gated channels are invasive and not feasible yet in humans. Thus, pharmacological or exercise strategies for manipulation of monoamines input onto motor neurones -such as blockade of 5-HT 2 receptors to attenuate F (Goodlich et al, 2023) or varying contraction intensities (Orssatto, Mackay et al, 2021, 2023 and the use of remote contractions to increase F (Orssatto, Fernandes et al, 2022) -could be further explored to understand the role of serotonin on age-related reductions in PICs.…”
Section: What Is Not Known About Pics With Respect To Ageing and Exer...mentioning
confidence: 99%